HJ11 decoction restrains development of myocardial ischemia-reperfusion injury in rats by suppressing ACSL4-mediated ferroptosis - Zhang, Fangyuan; Li, Ziyun; Gao, Ping; Zou, Jiaxi; Cui, Yuting; Qian, Yi; Gu, Renjun; Xu, Weiming; Hu, Jingqing (Frontiers in Pharmacology, 2022)
HJ11 is a novel traditional Chinese medicine developed from the appropriate addition and reduction of Si-Miao-Yong-An decoction, which has been commonly used to treat ischemia-reperfusion (I/R) injury in the clinical setting. However, the mechanism of action of HJ11 components remains unclear. Ferroptosis is a critical factor that promotes myocardial I/R injury, and the pathophysiological ferroptosis-mediated lipid peroxidation causes I/R injury. Therefore, this study explored whether HJ11 decoction ameliorates myocardial I/R injury by attenuating ACSL4-mediated ferroptosis. This study also explored the effect of ACSL4 expression on iron-dependent programmed cell death by preparing a rat model of myocardial I/R injury and oxygen glucose deprivation/reperfusion (OGD/R)–induced H9c2 cells. The results showed that HJ11 decoction improved cardiac function; attenuated I/R injury, apoptosis, oxidative stress, mitochondrial damage, and iron accumulation; and reduced infarct size in the myocardial I/R injury rat model. Additionally, HJ11 decoction suppressed the expression of ferroptosis-promoting proteins [Acyl-CoA synthetase long-chain family member 4 (ACSL4) and cyclooxygenase-2 (COX2)] but promoted the expression of ferroptosis-inhibiting proteins [ferritin heavy chain 1 (FTH1) and glutathione-dependent lipid hydroperoxidase glutathione peroxidase 4 (GPX4)] in the myocardial tissues of the I/R injury rat model. Similar results were found with the OGD/R-induced H9c2 cells. Interestingly, ACSL4 knockdown attenuated iron accumulation, oxidative stress, and ferroptosis in the OGD/R-treated H9c2 cells. However, ACSL4 overexpression counteracted the inhibitory effect of the HJ11 decoction on OGD/R-triggered oxidative stress and ferroptosis in H9c2 cells. These findings suggest that HJ11 decoction restrained the development of myocardial I/R injury by regulating ACSL4-mediated ferroptosis. Thus, HJ11 decoction may be an effective medication to treat myocardial I/R injury.